Reactive and tumor-like lesions of the oral cavity - Parviz Deyhimi; Mahdi Sabaghian; Faezeh Azmoodeh; Ali Tavakoli Hoseini (Isfahan University of Medical Sciences, 2011)
The oral cavity is always exposed to variable chronic and persistent irritations because of its special anatomic location and its various functions, such as chewing. Therefore, many lesions, referred to as reactive or tumor-like lesions, occur in the mouth as a result of these chronic and persistent irritations. Chronic irritating factors of the oral cavity include microbial, chemical and pharmaceutical agents, mechanical traumas, and endocrinal and hormonal factors. Given the role of local irritating factors, such as calculus, dental plaque and local traumas in inducing these lesions, elimination of these factors and agents should be undertaken by dental practitioners to prevent incidence or recurrence of such lesions. In addition, treatment of these lesions is possible by dental practitioners in many cases. Therefore, knowledge about differential diagnosis, treatment plan and prognosis of these lesions is mandatory for dental practitioners. Key words: Reactive lesions, Clinical features, Radiographic features, Histopatholigical features, Differential diagnosis, Treatment.